Transformasi Disiplin Spiritual Menjadi Karakter Tanggungjawab: Implementasi Kegiatan Muraja’ah di TKIT Daarul Hikmah Cianjur - Siti Sarifah; Siti Qomariyah; Dwi Suryani Kurniawan; Nura Nuraeni; Eni Nuraeni (IIQ An Nur Yogyakarta, 2026)
The formation of responsibility character in early childhood is an essential foundation for personality development that will influence their future lives. This study aims to analyze the implementation of muraja’ah activities in shaping the character of responsibility at TKIT Daarul Hikmah, Pacet District, Cianjur Regency. The phenomenon underlying this research is that many students have not yet demonstrated responsibility toward their tasks, especially in the context of highland socio-economic environments with uneven family support. The research employs a descriptive qualitative method through observation, in-depth interviews, and documentation studies using data triangulation techniques. The research focus includes the concept of muraja’ah, character formation strategies, activity implementation, as well as inhibiting factors and solutions. The results indicate that muraja’ah conducted every morning using talaqqi and Ummi methods successfully transforms spiritual discipline into responsibility character through a holistic integrative strategy. The implementation of muraja’ah trains children's Self-Regulated Learning (SRL) in the dimensions of self-observation, judgmental process, and self-response. The main obstacles, including school-home dissonance, differences in children's abilities, and time limitations, can be overcome through short learning sessions, enjoyable media, and intensive partnerships with parents. This study concludes that the success of responsibility character formation highly depends on the consistency of habituation at school and the continuity of guidance at home through structured parenting programs.